Deciphering a mitochondria-related signature to supervise prognosis and immunotherapy in hepatocellular carcinoma - Shi, Yanlong; Huang, Guo; Jiang, Fei; Zhu, Jun; Xu, Qiyang; Fang, Hanlu; Lan, Sheng; Pan, Ziyuan; Jian, Haokun; Li, Li; Zhang, Yewei (Frontiers in Immunology, 2022)
Hepatocellular carcinoma (HCC) is a major public health problem in humans. The imbalance of mitochondrial function has been discovered to be closely related to the development of cancers recently. However, the role of mitochondrial-related genes in HCC remains unclear. The RNA-sequencing profiles and patient information of 365 samples were derived from the Cancer Genome Atlas (TCGA) dataset. The mitochondria-related prognostic model was established by univariate Cox regression analysis and LASSO Cox regression analysis. We further determined the differences in immunity and drug sensitivity between low- and high-risk groups. Validation data were obtained from the International Cancer Genome Consortium (ICGC) dataset of patients with HCC. The protein and mRNA expression of 6 mitochondria-related genes in tissues and cell lines was verified by immunohistochemistry and qRT-PCR. The 6 mitochondria-related genes signature was constructed for better forecasting the prognosis and immunity, based on which patients were divided into high-risk and low-risk groups. The ROC curve, Nomogram and Calibration curve exhibited an admirable clinical predictive performance of the model. The risk score was associated with clinicopathological characteristics, and proved to be an independent prognostic factor in patients with HCC. The above results were verified in the ICGC validation cohort. Compared with normal tissues and cell lines, the protein and mRNA expression of 6 mitochondria-related gene were up-regulated in HCC tissues and cell lines. The signature could be an independent factor that supervises the immunotherapy response of HCC patients, and possess vital guidance value for clinical diagnosis and treatment.